Application of Electrochemical Impedance Spectroscopy to Evaluate Ripeness and Storage-Induced Quality Changes in Nutmeg (Myristica fragrans Houtt) - Ronaldo Talapessy; Gianita A. Salamena; Pricillia J. Sabandar; Tomoaki Ikegami (Green Engineering Society, 2025)
Nutmeg (Myristica fragrans Houtt) is an endemic fruit essential in the food industry; nevertheless, local farmers still rely on conventional methods to determine harvest time. The objectives of the research are to determine the freshness and ripening of nutmeg using the Electrochemical Impedance Spectroscopy (EIS) method. This study investigates the impedance of ripe and unripe nutmeg after five days of storage at 27°C and 4°C within a frequency range of 0–15 MHz. Ripe fruit has an impedance of 2-6 MW, lower than unripe fruit at 9-12 MW.. The high and steady impedance at low frequencies indicated the low moisture content and preserved cellular integrity of the ripe fruit. In contrast, the impedance of unripe fruits decreases gradually, indicating greater permeability and tissue disintegration. Advanced tissue breakdown reduces impedance despite decreasing water content, and these electrical changes are associated with mass loss from respiration and dehydration. The weight of nutmeg remains stable at lower temperatures but decreases at room temperature. The findings demonstrate that EIS is a rapid and non-invasive technique for assessing nutmeg maturity and postharvest quality, supporting more accurate prediction and improved storage management.